1996
DOI: 10.1007/bf01249620
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal motility disorders in patients with psychiatric disease

Abstract: Clinical and experimental observations indicate that the motility of the oesophagus may be affected by emotional stimuli. The aim of this study was to evaluate the incidence of oesophageal contractility impairment in patients suffering from a psychiatric disorder. Fifty-one patients admitted to the psychiatric department were submitted to an oesophageal transit study by means of krypton-81m. All patients with an abnormal oesophageal transit underwent manometry and endoscopy. The level of depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, an interesting question is whether MUNOD could disturb normal swallowing physiology. Roland et al evaluated the incidence of esophageal contractility disturbances in psychiatric patients [27]. Manometry showed a high percentage of functional motor impairment in patients with complaints of anxiety and/or depression, while endoscopy in these patients showed no structural abnormalities [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an interesting question is whether MUNOD could disturb normal swallowing physiology. Roland et al evaluated the incidence of esophageal contractility disturbances in psychiatric patients [27]. Manometry showed a high percentage of functional motor impairment in patients with complaints of anxiety and/or depression, while endoscopy in these patients showed no structural abnormalities [27].…”
Section: Discussionmentioning
confidence: 99%
“…Roland et al evaluated the incidence of esophageal contractility disturbances in psychiatric patients [27]. Manometry showed a high percentage of functional motor impairment in patients with complaints of anxiety and/or depression, while endoscopy in these patients showed no structural abnormalities [27]. In a large prospective population-based study, Koloski et al showed that anxiety is an independent predictor for new onset functional gastrointestinal disorders like irritable bowel syndrome, suggesting that affective disorders can underlie physical symptoms [28].…”
Section: Discussionmentioning
confidence: 99%
“…Manometry was performed on those with abnormal results, but two patients refused. The result was that 10 of the 11 tested patients had major motor abnormalities by manometry, indicating a relationship between psychiatric problems and motor disorders [23].…”
Section: Beck Depression Inventory and Beck Anxiety Inventory Assessm...mentioning
confidence: 96%
“…Kim, Chung H., et al's (1996) study found that depression and anxiety were not different among patients with dysphagia due to outflow obstruction, peristalsis disorders, and those without findings in endoscopy, barium or manometry. Roland et al (1996) evaluated 51 patients with psychiatric problems and upper GI somatization symptoms by esophageal transit time, 13 of whom had abnormal or delayed transit time. Manometry was performed on those with abnormal results, but two patients refused.…”
Section: Beck Depression Inventory and Beck Anxiety Inventory Assessm...mentioning
confidence: 99%
“…[4] It is possible that dysphagia can be part of a psychotic experience, namely a delusion of control or somatic passivity phenomenon. [5] There have also been a few reports that dysphagia/esophagial motility disorders are likely to be “inherent” in psychiatric disorders,[67] more so in Schizophrenia. [8] It is also a well-known fact that the prevalence of medical co-morbidity is significantly higher in mentally ill patients and hence an organic cause for dysphagia can never be ignored.…”
Section: Introductionmentioning
confidence: 99%